STRATEGI REKRUTMEN DALAM PENINGKATAN KINERJA KARYAWAN MEDIA PERS INDONESIA - Muhammad Alkirom Wildan; Ahmad Mustain Saleh; Mochamad Ali Imron (Insan Doktor Ekonomi Indonesia (IDEI), 2020)
The role of a qualified workforce is able to influence the level of performance of a company. With the high mobility of employees in the Press Media in Indonesia, factors in the recruitment and selection process of employees are also considered very important to know the value of employee performance. Seven criteria (seven criteria) that can be used as guidelines in the employee recruitment process include competence, ability, compatibility, commitment, character, culture, and compensation. This study used a qualitative approach with a combination of secondary data and in-depth observations and interviews with four informants from the editorial and non-editorial departments. The recruitment of Indonesian Press Media was carried out openly and in accordance with SOP with criteria that were only based on educational background, ability and commitment. The company had not applied all 7C criteria in the recruitment of prospective new employees. The management was of the opinion that the promotion strategy was not only based on merit but also needed to be taken into account by the length of service in the company. While according to the employee was work performance. Media Press Indonesia did not have clear concepts, instruments, and indicators, or standards for the recruitment of prospective employees and changes in career or employee positions. Peran tenaga kerja yang berkualitas mampu mempengaruhi tingkat kinerja suatu perusahaan. Dengan tingginya mobilitas pegawai di Media Pers di Indonesia, faktor dalam proses rekrutmen dan seleksi pegawai juga dinilai sangat penting untuk mengetahui nilai kinerja pegawai. Tujuh kriteria (tujuh kriteria) yang dapat dijadikan pedoman dalam proses rekrutmen pegawai meliputi kompetensi, kemampuan, kecocokan, komitmen, karakter, budaya, dan kompensasi. Penelitian ini menggunakan pendekatan kualitatif dengan kombinasi data sekunder dan observasi mendalam serta wawancara dengan empat informan dari bagian redaksi dan non redaksi. Rekrutmen Media Pers Indonesia dilakukan secara terbuka dan sesuai SOP dengan kriteria hanya berdasarkan latar belakang pendidikan, kemampuan dan komitmen. Perusahaan belum menerapkan seluruh kriteria 7C dalam rekrutmen calon karyawan baru. Manajemen menilai, strategi promosi tidak hanya berdasarkan merit tetapi juga perlu diperhitungkan dengan lamanya masa kerja di perusahaan. Menurut karyawan adalah prestasi kerja. Media Press Indonesia tidak memiliki konsep, instrumen, dan indikator, atau standar yang jelas dalam rekrutmen calon pegawai dan perubahan karir atau jabatan pegawai.